Interview with Joseph Vogl. Intellectual History and Political Economy of Modern Capitalism (interviewed by Ivan Boldyrev) - Joseph Vogl (Journal of Economic Sociology, 2019)
The contemporary positions of economic theory and the modern development of the capitalist system were the main topics of discussion with Prof. Joseph Vogl. Several questions were discussed regarding aesthetics, historical and political contexts, the temporality of economic knowledge, and its reflexivity. Prof. Vogl spoke about his studies aimed at the investigation of aesthetic representation and the poetics of economic models and abstractions in different genres, such as literature, theatre, and poetry. During the conversation, Prof. Vogl problematized the objectivity of conclusions in economic disciplines, while economics has not been considered in a historical context that forms an agenda. The author problematized the objectivity of conclusions that pretend to be in the economic discipline, although economics has not been considered as a historical context that forms its agenda. Prof. Vogl claimed that modern economic theory, like early political economy, is historically rooted in its agenda determined by the structure of power interests. Furthermore, the expansion process of financial markets represents the development of new forms of governmentality and institutional order. Through these forms, financial capital becomes the lender of last resort, which is not subordinate to central banks and federal governments.